Conservative treatment for right ventricular free wall rupture in a patient with acute myocardial infarction - Mohd Firdaus, Mohd Al-Baqlish; Abdul Rahim, Nur Syahirah; Rusdi, Nurtasneem; Idris, Nor Saadah; Mohd Said, Mohd Ridzuan; Zainal Abidin, Imran (HIndawi, 2020)
Ventricular wall rupture possesses a high mortality rate in patients with acute myocardial infarction. We presented a case of a ninety-year-old gentleman who presented with acute inferolateral myocardial infarction in cardiogenic shock and right ventricular free wall rupture. He was treated conservatively and survived.